External Validation of Belgian Outcome of Burn Injury Score on Burned Patient In Burn Unit dr. Cipto Mangunkusumo General Hospital - Karlie, John; Wardhana, Aditya (UI Scholars Hub, 2017)
Introduction. The scoring system in burns is a merit in predicting mortality. To date, there’s no scoring system used as a standard prognostic tool at Cipto Mangunkusumo General Hospital’s Burn Unit. Belgian Outcome of Burn Injury (BOBI) Score, one of the best scoring systems in accordance to systematic review in 2013 was validated externally in a study. Method. A retrospective cohort study was conducted enrolling all burn patients managed during period of 2012 to 2013 in burn unit of Cipto Mangunkusumo General Hospital. The prediction model of BOBI score (age, total burned surface area, and inhalation injury) were variables to be analyzed statistically. ROC and AUC was analyzed to find out its accurate level of prediction. The strong AUC is found with the value of >80– 90%. Results. Out of 304 subjects enrolled, the mean age was 28 years, mean TBSA was 29%, inhalation injury was 15.7%, and overall mortality was 17.7%. The model gave an accurate prediction of mortality. The receiver operating characteristic analysis demonstrated an area under the curve of 0.96 (95% CI 0.94–0.99). Conclusion. The mortality prediction model (BOBI score) demonstrated a good accuracy. This model provide a good prediction tool and could be implemented in our burn management.